Pengaruh E-Service Quality dan Perceived Value TerhadapRepurchase Intention dengan Customer Satisfaction SebagaiVariabel Intervening pada Aplikasi Online Grocery Shopping - Rachma Kuntoro, Mutiara; Rizan , Mohamad; Krissanya , Nofriska (Teewan Journal Solutions, 2025)
The present study aims to determine the effect of:1) E-service quality on customer satisfaction.2) Perceived value on customer satisfaction.3) E-service quality on repurchase intention.4) Perceived value on repurchase intention.5) Customer satisfaction on repurchase intention.6) E-service quality on repurchase intention through customer satisfaction.7) Perceived value on repurchase intention through customer satisfaction. Data was collected through the administration of online questionnaires disseminated via social media platforms.The study's participants were residents of DKI Jakarta, aged between 18 and 55 years, who had conducted transactions on Astro within the preceding year.The final data set comprised 200 respondents, and the analysis was conducted using SPSS and SEM (Structural Equation Modelling) on Lisrel. The results of this study are in accordance with the hypothesis, where e-service quality has a positive and significant effect on customer satisfaction, perceived value has a positive and significant effect on customer satisfaction, and e-service quality has a positive and significant effect on repurchase intention, perceived value. The study also demonstrates a positive and significant relationship between customer satisfaction and repurchase intention, as well as a significant effect of e-service quality on repurchase intention through customer satisfaction. Furthermore, the study reveals a positive and significant effect of perceived value on repurchase intention through customer satisfaction.